2020
DOI: 10.1186/s13195-020-00702-6
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET hypermetabolism is associated with higher tau-PET in mild cognitive impairment at low amyloid-PET levels

Abstract: Background FDG-PET hypermetabolism can be observed in mild cognitive impairment (MCI), but the link to primary pathologies of Alzheimer’s diseases (AD) including amyloid and tau is unclear. Methods Using voxel-based regression, we assessed local interactions between amyloid- and tau-PET on spatially matched FDG-PET in 72 MCI patients. Control groups included cerebrospinal fluid biomarker characterized cognitively normal (CN, n = 70) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 58 publications
6
32
0
Order By: Relevance
“…Interestingly, we found that the early cognitive benefit associated with the ε4 allele is mainly in executive function (reasoning, phonemic fluency), while no difference was observed for memory or semantic tasks which involve temporal and temporal intern area. This is consistent with several metabolic PET imaging studies which have found that APOE ε4 allele in the normal population is associated with a decrease in metabolism in the posterior regions of the brain (parietal, posterior cingulate), but also with an increase of metabolism in the anterior frontal area [42,43]. A recent meta-analysis of studies on the age range from 2 to 40 years did not find differences in cognitive performance between APOE ε4 carriers and noncarriers, with the authors concluding that there was no support for the antagonistic pleiotropic hypothesis [20].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, we found that the early cognitive benefit associated with the ε4 allele is mainly in executive function (reasoning, phonemic fluency), while no difference was observed for memory or semantic tasks which involve temporal and temporal intern area. This is consistent with several metabolic PET imaging studies which have found that APOE ε4 allele in the normal population is associated with a decrease in metabolism in the posterior regions of the brain (parietal, posterior cingulate), but also with an increase of metabolism in the anterior frontal area [42,43]. A recent meta-analysis of studies on the age range from 2 to 40 years did not find differences in cognitive performance between APOE ε4 carriers and noncarriers, with the authors concluding that there was no support for the antagonistic pleiotropic hypothesis [20].…”
Section: Discussionsupporting
confidence: 92%
“…A recent study including subjects with mild cognitive impairment showed that higher tau-PET uptake was associated with higher glucose metabolism in patients with lower levels of amyloid-PET uptake. This finding resulted to be associated with lower memory performance [ 30 ]. A study focused on the identification of a brain 18 F-FDG-PET Parkinson’s disease–related pattern (PDRP) showed that the typical PDRP topography was characterized by relative hypermetabolism in the thalamus, putamen/pallidum, pons, cerebellum, and motor cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the inclusion of the amyloid-negative subjects in this study might interfere with the exploration of FDG cascade. The conflicting relationship between tau and glucose metabolism has been reported in amyloid negative MCI, where FDG hypermetabolism was associated with higher tau PET [ 34 ]. However, apart from results indicated by logistic regression, [ 18 F]FDG SUVr decreases in late pseudo-time , as illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%